Faktor Faktor Yang Mempengaruhi Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Belo Tahun 2021 - Nurbaniy, Nurbaniy (Barongko: Jurnal Ilmu Kesehatan, 2023)
According to the World Health Organization (WHO) defines pregnancy anemia as hemoglobin levels of less than 11 grams or less than 33% at any time in pregnancy that considers hemodilution that normally occurs in pregnancy where hemoglobin levels are less than 11 grams in the first trimester (Proverawati, 2018). Analytic descriptive research method, with a cross sectional study approach. The study population was 78 and the sample was 42 respondents with simple accidental sampling technique. Statistical test using chi- square test. Research results: There is a relationship between knowledge about factors that affect the incidence of anemia in pregnant women in the work area of the Belo Health Center which is shown by the majority of respondents' knowledge, namely lack of knowledge as many as 33 respondents (80.5%) and shown by the age of respondents who are at risk as many as 31 respondents (75.6%) and, shown by the age of pregnancy as much as 26 respondents (63.4%), shown by parity as much as 26 respondents (63, 4%), indicated by work as most of them do not work, namely 33 respondents (80.5%), indicated by the status of SEZs as most of them are SEZ as many as 29 respondents (70.7%), indicated by education as most of them have junior high school education, namely 17 respondents (41.5%), Based on the chi-square test, it is found that there is a relationship between the level of knowledge, age of pregnant women, education, parity, occupation, pregnancy age, SEZ status, and the status of anemia incidence in the Belo Health Center working area in 2021. So it is necessary to conduct counseling by the Belo Health Center about the importance of preventing anemia to increase the level of knowledge in pregnant women and it is necessary to hold anemia understanding education, especially in dealing with the status of anemia incidence in pregnant women.